Asymmetric correlations in gold and other financial markets. Issue 46 (1st October 2016) - Miyazaki, T.; Hamori, S.
ABSTRACT: In this article, we implement a recently developed statistical method to test asymmetries in cross-asset correlations, focusing in particular on the gold market. Our empirical results provide evidence that gold exhibits asymmetric correlations with stocks and the U.S. dollar, but not with bonds. Furthermore, splitting the sample into three characteristic periods, we find that exceedance correlations exhibit substantial time variation even in similar market tensions for same pairs of assets. Our findings imply that investors and fund managers should take into account the asymmetric dependence structure, which depends on the upside or downside of the market.